Neuropsychological Disorders Indicative of Postresuscitation Encephalopaty in Rats - Gorenkova, Natalia A.; Nazarenko, Irina V.; Volkov, Aleksandr V.; Avruschenko, Maria Sh.; B. Lapa, Gennady; Kovalev, Georgi I.; Molchanova, Lidia V. (The Spanish Journal of Psychology, 2005)
The aim of this research was to study the effect of 12-minute clinical death on innate and acquired behavior, biogenic amine concentration, and the composition and quantity of neural populations in specific brain regions of white rats. The study shows that in animals during the postresuscitation period with formal restoration of neurological status, there are changes in emotional reactivity, orientation-exploration reactions, impairment of learning and memory, decrease in exercise tolerance and pain sensitivity. These processes are accompanied by alterations in serotonin and norepinephrine levels in the frontal cerebral cortex, dopamine and serotonin levels in the striatum, certain biochemical indices in blood plasma and neural loss in the CA1 sector of the hippocampus and lateral portions of the cerebellum.
Keywords: neuropsychological disorders; clinical death; postresuscitation encephalopaty; emotional reactivity; orientation-exploration reaction; biogenic amines; neuronal population